2017
DOI: 10.19044/esj.2016.v13n3p171
|View full text |Cite
|
Sign up to set email alerts
|

Female Dental Student’s Perception of Their Dental Aesthetics and Desired Dental Treatment

Abstract: Objectives: This study aims to assess the self-perception of female dental students of their dental aesthetics regarding their satisfaction, its effect on their quality of life and felt need for treatment. Materials and Method: This is a descriptive study for 1st, 2nd and 3rd year dental students (n=110) in the College of Dentistry at Princess Nourah University (PNU). The survey was distributed via link "Google form". A 20 item questionnaire was prepared and tested before on seven students for clarity. Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Similarly, the majority (98.3%) of respondents in our study accepted that the smile is one of the main aesthetic features of the face. In a study by Abidia et al , the majority (89.4%) of female students considered that their teeth determined their facial attractiveness; almost one third (30.8%) reported trying to hide their smile, nearly one half (51%) were not satisfied with the colour of their teeth, and around two thirds (61.5%) felt that their quality of life was affected by their dental appearance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the majority (98.3%) of respondents in our study accepted that the smile is one of the main aesthetic features of the face. In a study by Abidia et al , the majority (89.4%) of female students considered that their teeth determined their facial attractiveness; almost one third (30.8%) reported trying to hide their smile, nearly one half (51%) were not satisfied with the colour of their teeth, and around two thirds (61.5%) felt that their quality of life was affected by their dental appearance [31].…”
Section: Discussionmentioning
confidence: 99%
“…The use of veneers in esthetic dentistry has evolved into the discovery of this terminology, which is now being used by patients as well as dental practitioners on a regular basis. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…The major factor influencing research is the background knowledge of subjects as faculty of dentistry students who tend to pay more attention to dental aesthetics during their university studies, a fact obviously affecting their perception of facial aesthetics. 8 This conclusion is also supported by research into the perception and level of satisfaction regarding dental aesthetics on the part of students in Saudi Arabia which showed that, based on a satisfaction assessment index, no differences exist between satisfaction levels in males and females regarding their dental aesthetics. 18 Age control and orthodontic treatment experiences also influence the assessment result of the subject.…”
Section: Discussionmentioning
confidence: 80%
“…Available at http://e-journal.unair.ac.id/index.php/MKG DOI: 10.20473/j.djmkg.v51.i4.p200-204 of tooth display. 8 It has been found that females tend to be less satisfied with their smiles than males, rendering them generally more aware, sensitive and concerened when it comes to appearance. It is, thus, proven that females pay more attention to aesthetics.…”
Section: Introductionmentioning
confidence: 99%